Thyroid function and liver fibrosis: FT3 levels are inversely and independently correlated with enhanced liver fibrosis score in solid organ transplant patients with dysglycemia - Leanza, Claudia; Giusti, Maria Ausilia; Miceli, Vitale; Zito, Giovanni; Tinnirello, Rosaria; Iannolo, Gioacchin; Galante, Antonio; Emanuele, Fabrizio; Amato, Marco; Lo Iacono, Giovanna; Lo Re, Vincenzina; Gruttadauria, Salvatore; et al. (Frontiers in Immunology, 2026)
BackgroundSolid organ transplantation (SOT) is frequently complicated by dysglycemia and metabolic dysfunction–associated steatotic liver disease (MASLD), conditions that accelerate the development of liver fibrosis. Given the recognized thyroid–liver crosstalk, we investigated the association between thyroid function and the enhanced liver fibrosis (ELF) score in SOT recipients with diabetes or prediabetes.MethodsSeventy-one adult SOT recipients with diabetes or prediabetes, with ultrasound evidence of liver steatosis and/or a FIB-4 > 1.3, underwent standardized clinical phenotyping, biochemical profiling, thyroid hormone measurements, ELF testing, and liver stiffness measurement (LSM). Associations with ELF were assessed using correlation analyses and multivariable linear regression adjusted for age, sex, body mass index (BMI), transaminases, glycated haemoglobin, creatinine, haemoglobin, albumin, immunosuppressive drugs, glucagon-like peptide-1 receptor agonist (GLP-1RA) therapy, and transplanted organ type.ResultsParticipants had a mean age of 63.1 ± 9.5 years and BMI of 27.8 ± 4.8 kg/m². Mean ELF was 9.21 ± 1.00 (low risk <9.8: 70%; intermediate 9.8–11.3: 27%; high ≥11.3: 3%). ELF correlated positively with age (r=0.43, p=0.0002), aspartate aminotransferase (AST; r=0.50, p<0.0001), alanine aminotransferase (ALT; r=0.33, p=0.0059) and creatinine (r=0.39, p=0.0009), and inversely with haemoglobin (r=−0.39, p=0.0009), albumin (r=−0.38, p=0.0024), controlled attenuation parameter (CAP) (r=−0.29, p=0.0171). Among thyroid variables, free triiodothyronine (FT3) correlated inversely with ELF score (r=−0.45, p=0.0003), while TSH and FT4 showed no significant association with ELF score (r=0.00, p=0.9859; r=-0.5, p=0.6891). In multivariable analysis (R²=0.67; p=0.0002), lower FT3 (β=−0.611 ± 0.288; p=0.0404) and age (β=0.029 ± 0.012; p=0.0304) remained independently associated with higher ELF. No association was found between ELF and LSM.ConclusionsIn SOT recipients with dysglycemia lower FT3 levels were independently associated with increased ELF scores. This finding suggests a potential link between subtle variations in thyroid function and markers of fibrogenic activity in metabolically vulnerable transplant recipients. Prospective studies are warranted to elucidate the causal directionality of this association and its clinical relevance.